Aesthetic Morphology of Animation - Wikayanto, Andrian; Damayanti, Nuning Yanti; Grahita, Banung; Ahmad, Hafiz Aziz (Harmonia: Journal of Arts Research and Education, 2023)
Aesthetic morphology does not judge whether a work is good or bad but is a study of form in art that focuses on description, comparison, and stylistic analysis. Aesthetic morphology emphasizes great attention to the discussion of form, content, and style. However, this theory is still general, and there needs to be more research that explicitly discusses how it applies to animated artworks. This research will use the Comprehensive Literature Review (CLR) method. CLR is a methodological approach for critical and in-depth research activities on a particular topic in several stages of the research process. The CLR research process consists of three phases: exploration, interpretation, and dissemination. The result of this research is that the form consists of aspects of animation design, movement and kinetics, and sound and structural design. The content aspect consists of 2 main elements: story and character. Meanwhile, the style aspect is influenced by two main elements, namely the technology used in the production process and the appearance of the animation. The results of this research are expected to be used to explore the characteristics of animation works of certain creators, countries/locations, or periods in the history of the development of the aesthetic form of animation in the world.